Queens of the Wild: Pagan Goddesses in Christian Europe, by Ronald Hutton - Cusack, Carole M. (International journal for the study of new religions, 2023)
Queens of the Wild: Pagan Goddesses in Christian Europe, by Ronald Hutton. New Haven and London: Yale University Press, 2022. Hb. x + 245 pp. US$86.95. ISBN: 9780300261011